2008
DOI: 10.1007/s00256-008-0569-6
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic findings and therapeutic embolization of late hemarthrosis after total joint arthroplasty

Abstract: Angiography for late spontaneous hemarthrosis is very effective to exclude or establish vascular malformations and to establish the diagnosis of hypertrophic vascular synovium. Selective arterial embolization seems to be a good therapeutic option as alternative to open or arthroscopic synovectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 11 publications
2
21
0
Order By: Relevance
“…Spontaneous hemarthrosis after hip or knee arthroplasty is rare, but it can be painful and debilitating [2,3,10,11]. The timing is variable, occurring from days to years after the index arthroplasty, as we observed and as prior studies have suggested [6,10].…”
Section: Discussionsupporting
confidence: 53%
“…Spontaneous hemarthrosis after hip or knee arthroplasty is rare, but it can be painful and debilitating [2,3,10,11]. The timing is variable, occurring from days to years after the index arthroplasty, as we observed and as prior studies have suggested [6,10].…”
Section: Discussionsupporting
confidence: 53%
“…Considerations for choosing an embolic agent are speed and reliability of delivery, duration of occlusion and preservation of normal tissue. 8,20,28,35,36 Coils are highly radiopaque, and ideal for single and large vessel occlusion. 18e20,25 Coils can be deployed as a strut and combined with gelatin sponge or particles as occlusion agents.…”
Section: Discussionmentioning
confidence: 99%
“…18e20,25 Coils can be deployed as a strut and combined with gelatin sponge or particles as occlusion agents. 28 The use of gelatin sponge alone has the disadvantage of temporary embolic effect; thus, recurrent bleeding may occur. 16,19,27 For multiple lesions and distal location, particles can be used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8 Because aspiration may not fully resolve a patient's symptoms, further management must be tailored to the potential underlying etiology of the hemarthroses. In the post-TKA setting, arthroscopic 6 and angiographic investigations 11 often reveal a hypertrophic synovium as the underlying mechanism, though other causes have been reported including: arteriovenous fistula of the geniculate vessels, 3 pseudoaneurysm of geniculate vessels, 27 angiosarcoma, 4 impingement of vascular structures under meniscal remnants, 2 and implant malposition. 27 It is pertinent for the surgeon faced with recurrent hemarthroses following TKA to thoroughly consider these various etiologies, as they may guide further management.…”
Section: Clinical Significancementioning
confidence: 99%